(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Dr. Basu Venkateswara Reddy, Professor and Head, Department of Pharmaceutics, Sri.K.V.College of Pharmacy, Chikkaballapura, Karnataka, India Abstract The management of respiratory disorders is structured around algorithms that differentiate disease states and guide stepwise therapeutic intervention. Asthma management follows a control-based approach, stratifying patients into steps that dictate the use of inhaled corticosteroids (ICS) and bronchodilators, with a modern emphasis on ICS-formoterol as both a controller and reliever. The algorithm for Chronic Obstructive Pulmonary Disease (COPD) is based on the GOLD classification, using symptom burden and exacerbation history to guide the use of short- and long-acting bronchodilators (LAMA/LABA), with ICS reserved for patients with eosinophilic phenotypes. Pneumonia treatment algorithms are initiated by assessing severity (e.g., CURB-65) to determine the site of care, followed by empiric antibiotic selection based on likely pathogens and patient risk factors, with a mandate for timely de-escalation. The acute algorithm for pulmonary embolism is driven by hemodynamic stability and right ventricular strain, with risk stratification determining the use of anticoagulation, systemic thrombolysis, or embolectomy. Tuberculosis management is distinctly bifurcated into treatment for latent infection, which is a preventive algorithm, and active disease, which requires a prolonged, multi-drug regimen (RIPE) under directly observed therapy to ensure cure and prevent resistance. Keywords: Respiratory Algorithms, Asthma, COPD, Pneumonia, Pulmonary Embolism, Tuberculosis VIEW PDF